Ketimpangan Sosial dalam Novel Pincuk Garing karya Tulus Setiyadi - Fajarwati, Kinanti Dwi; Widagdo, Sungging; Anggraeni, Sri Prastiti Kusuma (Lingua Susastra, 2025)
The issue of social inequality in Indonesia remains a critical topic, particularly concerning access to education, the economy, and social justice, which are often marginalized in rural communities. This phenomenon is also reflected in literary works, including the novel Pincuk Garing by Tulus Setiyadi. This study aims to explore the manifestations of social inequality as depicted in the novel. The central research question concerns how forms of social inequality are represented through the characters and their relationships within the narrative. This research adopts a qualitative descriptive method with an objective literary approach, employing Pierre Bourdieu’s theory of capital (economic, cultural, social, and symbolic) to identify various forms of capital, alongside Robert Stanton’s theory of story facts to analyze how these capitals are embedded in character construction and depiction. The findings reveal a disproportionate distribution of capital: economic (12 instances, 31%), cultural (6 instances, 15.3%), social (8 instances, 20.5%), and symbolic (13 instances, 33.3%). This imbalance directly influences disparities in power, recognition, and opportunity, wherein characters with greater capital are portrayed as dominant, while those with limited capital are frequently marginalized. These findings underscore the significant role of literature as a mirror of social realities and contribute to addressing gaps in existing scholarship by applying Bourdieu’s capital theory to Pincuk Garing, thereby offering a comprehensive analysis of multidimensional social inequality.